Resistance in Postwar France: Five New and Noteworthy Histories. (February 2023) - Conklin, Alice L.
Abstract : Historians of modern Europe have long seen the tragic events of the Second World War in France as a major caesura in the history of that nation. But eighty years later, do the legacies of the war still help us understand postwar France and its political divisions? The five superb books under review make a strong case that the fracturing experiences of defeat, Vichy and the Resistance shaped some of the most important subsequent developments in France in ways that previous historians have failed to recognise. The developments identified by these authors include the waxing and waning of Resistance myths as part of a contested deportation memory landscape, an anti-authoritarian résistant psychiatry born in 1940 that went on to revolutionise French theories of alienation in the face of both Stalinism and postwar capitalism, and rural resistance to the state-led transformation of the countryside as part of France's postwar economic modernisation. Collectively they point to a larger takeaway for historians of postwar Europe: oppositional movements in France may resemble similar movements elsewhere in a Western context marked by Cold War tensions and, more recently, globalisation; but these protests are also always following a script haunted in part by the trauma of France's war years – a past that has not passed, even eight decades later.